Deaf Weight Wise: A novel randomized clinical trial with Deaf sign language users. Issue 4 (8th March 2023) - Barnett, Steven; Matthews, Kelly; DeWindt, Lori; Sutter, Erika; Samuel‐Hodge, Carmen; Yang, Hongmei; Pearson, Thomas A.; ,
Abstract: Objective: The goal of this study was to address the absence of evidence‐based weight‐control programs developed for use with Deaf people. Methods: Community‐based participatory research informed the design of the Deaf Weight Wise (DWW) trial and intervention. DWW focuses primarily on healthy lifestyle and weight through change in diet and exercise. The study enrolled 104 Deaf adults aged 40 to 70 years with BMI of 25 to 45 from community settings in Rochester, New York, and randomized participants to immediate intervention ( n  = 48) or 1‐year delayed intervention ( n  = 56). The delayed intervention serves as a no‐intervention comparison until the trial midpoint. The study collected data five times (every 6 months) from baseline to 24 months. All DWW intervention leaders and participants are Deaf people who use American Sign Language (ASL). Results: At 6 months, the difference in mean weight change for the immediate‐intervention arm versus the delayed‐intervention arm (no intervention yet) was −3.4 kg (multiplicity‐adjusted p  = 0.0424; 95% CI: −6.1 to −0.8 kg). Most (61.6%) in the immediate arm lost ≥5% of baseline weight versus 18.1% in the no‐intervention‐yet arm ( p  < 0.001). Participant engagement indicators include mean attendance of 11/16 sessions (69%), and 92% completed 24‐month data collection. Conclusion: DWW, a community‐engaged, culturally appropriate, and language‐accessible behavioral weight loss intervention, was successful with Deaf ASL users.